Islamic Character Education in Hajj Material Book Fikih Madrasah Ibtidaiyah Class 5 - Nesa Ramadanti; Ayu Kusumayanti Pramono; Rizka Nur Azzizah; Zakiyatul Fkriyah Nailal Muna; Andi Prastowo (Universitas Ahmad Dahlan, 2022)
Education is one of the things that underlies the formation of character. Furthermore, have the curriculum and learning materials been designed in a balanced way to bring out Islamic character values? So, things related to learning must also have a positive value without the subject matter to be delivered. Therefore, this study aims to determine the values contained in the material for Hajj that can be used as Islamic character education for elementary school-age children. The method used in this research is descriptive qualitative to show and describe the facts that exist in the research subject. This type of research is also included in library research. Sources of data used in the study are primary and secondary data and data analysis techniques using content analysis techniques by analyzing the material for Hajj for class 5 MI/SD. The primary data source in this study is the 5th grade MI Fiqh Book published by the Ministry of Religion. The results of this study indicate that the 5th grade MI/SD Hajj material presents activities with positive values that can be used as education so that some Islamic characters grow in every process that is in the Hajj. Such as patience, tolerance, sincerity, perseverance, and discipline. From the analysis of the research results, it can be concluded that the material for Hajj for grade 5 MI/SD is suitable as an Islamic character education material for children.